Effect of film - wrapping and refrigeration on postharvest shelf-life of eggplant fruits cv. Ciça - Henz, Gilmar P.; Silva, Claudia (Pesquisa Agropecuaria Brasileira, 1995)
Fruits of eggplant cv. Ciça, a new hybrid released by CNPH/Embrapa, were evaluated for their postharvest shelf-life. Fruits were stored under four temperatures (4, 8, 12 and 24 °C) and different ways of packing (PVC film-wrapping; perforated PVC film-wrapping; and without wrapping). The experimental design was a completely randomized block, with four replications (nine fruits/parcel, arranged in a set of three fruits when film-wrapped). Each two days, the fresh weight loss, deterioration and the occurrence of chilling injury were evaluated. After 16 days of storage, the fresh weight loss in those fruits not wrapped ranged from 10.85 (4 °C) to 17.95% (24 °C), and from 1.69 (4 °C) to 5.95% (24 °C) in PVC film-wrapped fruits. After the 4th day, unwrapped fruits stored at 4 and 8 °C begun to show chilling symptoms. Fruit deterioration was bigger in wrapped fruits kept at 4 and 8 °C and also in all treatments kept at 24 °C. After 16 days, the best treatment for maintaining fruit quality of eggplant cv. Ciça was temperature of 12 °C and PVC film-wrapping, perforated or not, losing respectively 1.79 and 1.81% of fresh weight, with 0% of fruit deterioration and without symptoms of chilling injury.